2010
DOI: 10.1002/jsfa.4039
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of L(+)-lactic acid production from cassava wastewater by Lactobacillus rhamnosus B 103

Abstract: The use of cassava wastewater for cultivation of L. rhamnosus is feasible, with a considerable production of lactic acid. Furthermore, it is an innovative proposal, as no references were found in the scientific literature on the use of this substrate for lactic acid production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Sources of nitrogen are necessary for the synthesis of lipids, enzymes, amino acids, carbohydrates, and other substances (Coelho et al, 2010). According to Wood and Holzapfel, (1955), a source of nitrogen is the most influential factor in the growth of Lactobacillus.…”
Section: Resultsmentioning
confidence: 99%
“…Sources of nitrogen are necessary for the synthesis of lipids, enzymes, amino acids, carbohydrates, and other substances (Coelho et al, 2010). According to Wood and Holzapfel, (1955), a source of nitrogen is the most influential factor in the growth of Lactobacillus.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CSL may be used to replace YE because the high cost of YE has a negative impact on industrial processes (Oh et al, 2005). It is known that CSL has in its composition proteins, amino acids, B vitamins and other nutrients (Marták et al, 2003) and has been widely studied for supplementation in fermentation processes (Coelho et al, 2010). Wee et al (2004) evaluated the productivity, yield, consumption of sugar and production of L (+)-LA by Enterococcus faecalis RKY1 using 200 g/L molasses (equivalent to 102 g/L glucose) under different pH (5 to 9).…”
Section: La (G/l)mentioning
confidence: 99%
“…Srivastava et al (2015) obtained with cane molasses a maximum concentration of 55.89 g/L using Lactobacillus delbrueckii NCIM 2025. Coelho et al (2010) reported that the cassava wastewater for the production of lactic acid by Lactobacillus rhamnosus B 103 produceds lactic acid of 41.65 g/L after 48 h of fermentation. John et al (2008) reported 40 g/L lactic acid production with a productivity of 0.42 g/L.h from cassava bagasse via genetically modified Lactobacillus delbrueckii.…”
Section: Validation Of the Modelmentioning
confidence: 99%